(untitled) (Abuja Journal of Sociological Studies, 2026)
Kidnapping is a global problem and Nigeria in general and Abuja in particular is no exception with Kidnapping. This study explores the prevalence and pattern of kidnapping with the view of preventing and combating kidnappings in Abuja. A survey research design was adopted for the study using Taro Yamane sample size formula to arrive at the sample size of 400 residentsdrawn across 20 communities in 2 Area Councils of Abuja using a six- stage multistage sampling method to administer questionnaire and 27 participants comprising police officers and community leaders purposively selected for in-depth interviews. The descriptive statistics of percentages and frequency tables were used to analyze the quantitative data and thematic content analysis to analyze the qualitative data. The findings revealed a significant prevalence of kidnapping as a major security challenge with the rural communities as the black spots and hub for kidnapping. Also, the kidnappings committed by strangers, criminal gangs and militia, friends and acquaintances, and family members and relatives were most prevalent and committed anytime of the day and took place at various places, mostly along the roads, at residence, and farms in various communities; and executed mainly as an organized criminal gang activity. Therefore, it is concluded that kidnapping is pervasive and perpetrated by diverse parties and executed anytime of the day and at various places as an organized criminal gang activity in Abuja. For recommendations, job creation, adequate funding of security agencies, deployment of technology and public sensitization was suggested to prevent and combat kidnapping.